World War II as Inspiration for Digital Illustration - Aziz Abdurrahman Ash Shiddiq; Arif Fiyanto (Gorga : Jurnal Seni Rupa, 2025)
World War II (1939-1945) was one of the most influential events of the twentieth century, leaving enduring impacts on global politics, society, and culture. Beyond its devastation, the war has inspired artistic responses that attempt to convey both its trauma and its lessons. Among contemporary practices, digital illustration provides unique opportunities to reconstruct and reinterpret the past through flexible use of visual elements such as color, texture, composition, and atmosphere. This article explores semi-realistic digital painting techniques to represent two pivotal moments of World War II: the German invasion of Poland in 1939, which marked the beginning of the conflict, and Germany’s defeat in Berlin in 1945, which signaled its end in Europe. The creative process followed three stages: (1) historical analysis and concept design, (2) digital production, and (3) presentation to the audience. Historical references, including photographs, military symbols, and battlefield conditions, were utilized to maintain narrative accuracy while still allowing for artistic expression and symbolism. The two works are presented as a visual narrative that traces the war’s trajectory, from its dark outbreak to its symbolic conclusion. By employing contrasting tones, dynamic compositions, and evocative perspectives, the illustrations aim to evoke emotion, encourage reflection, and contribute to the preservation of collective memory. Ultimately, this study highlights the potential of digital illustration not only as a contemporary creative practice but also as a valuable medium for history education, cultural preservation, and interdisciplinary discourse.